If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + -6x = 61 + -2x Solving 37 + -6x = 61 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 37 + -6x + 2x = 61 + -2x + 2x Combine like terms: -6x + 2x = -4x 37 + -4x = 61 + -2x + 2x Combine like terms: -2x + 2x = 0 37 + -4x = 61 + 0 37 + -4x = 61 Add '-37' to each side of the equation. 37 + -37 + -4x = 61 + -37 Combine like terms: 37 + -37 = 0 0 + -4x = 61 + -37 -4x = 61 + -37 Combine like terms: 61 + -37 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| -3(6y-7)-y=-3(y-2) | | 5x^9*2u*2u^2x^9= | | 7(7n+3)-10(n-9)= | | 3/10t=6 | | y-13=-4 | | 0=8r-3r | | 2(a+1)=3(a-2)-a | | 3m+6=-6+m | | 10+m/2=6 | | q=-45/-3 | | 2(x+4)-5(x-3)=34 | | 6x-6-8=4x-4+6-2x | | 8+7x=78 | | 5n+7n=-12 | | 6+15y-3=8y+107-6y | | 5(a-12)-24=3(s+2) | | 5x-7-3x=19 | | (8t+30)+(-2-16)=-22 | | (x-5)/(2)=(x+2)/(3) | | (-11)(-15)=y | | 7p-5(3+p)= | | 6.42-10d=25 | | 6x^2+45x=180 | | 2(3t-8)-4t=2 | | -x-12=45 | | 1-8m=-5m+16 | | 8a-4-4a=6-a | | 3x-11=30 | | x/2+2/3=3/4 | | v=x(25-2x)(12-2x) | | 7p-5(3+p)=7p-15-5p | | -16=4a+2a |